PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSAEFEK INDONESIA PERIODE 2011-2015 - Mochamad Nadief Kaelani; Siagian, Arifin (Pasca Sarjana Universitas Satya Negara Indonesia, 2017)
The objective of the research is to analyze the influence of financial performance to share price of mining companies listed at Indonesian Capital Market during 2011-2015. The method used in the research is descriptive method analysis with quantitative approach. The technique used to select samples was perposive sampling, derived from 8 mining companies. The data were analyzed using panel data analysis in the form of random effect regression. The result of the study indicates that partially the Return on Equity (ROE) and Return on Assets (ROA) have positive and significant influence to Share Price of mining companies during 2011-2015 at α=0.10 and α=0.05. The other variables, Debt to Equity Ratio (DER) and Book Value per Share (BVPS), are not significantly influence to Share Price of mining companies during 2011-2015 at α=0.05. Simultaniously, all variables (ROE, ROA, DER, and BVPS) have positive and significant influence to Share Price of mining companies during 2011-2015 at α=0.05. The determination coefficient (R 2) in this study was 0.85209 which imply that the ability of independent variables in explaining the variation of dependent variable was 85,20%; while the remaining 14,80% was explained by other independent variables outside the model.